PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN KEUANGAN DESA TERHADAP PEMBANGUNAN DESA (STUDI KASUS DI DESA PALUH MANIS, KECAMATAN GEBANG, KABUPATEN LANGKAT) - MAJU SIREGAR (LP2MTBM MAKARIOZ, 2020)
The objective research to examine the influence of accountability, transparency and public participation in village financial management of village development. The population in this study were people who participated in village development meetings in Paluh Manis Village, Gebang District, Langkat Regency. The method used in this study was purposive sampling method, and the number of samples obtained was 36 people. The type of research used is quantitative research. The results of this study indicate that based on the t test or partial test of accountability, transparency and public participation partially and significantly influence village development, based on the Simultaneous F test shows that the variables of accountability, transparency and publicparticipation jointly have a significant influence on village development. This research is expected to be able to provide useful input for the Village Government to work together in order to further increase transparency, accountability, and public participation in village financial management so as to further enhance village development into a developed and developing village.